The Prevalence of Migraine With Anxiety Among Genders - Karimi, Leila; Crewther, Sheila Gillard; Wijeratne, Tissa; Evans, Andrew E.; Afshari, Leila; Khalil, Hanan (Frontiers in Neurology, 2020)
Objective The aims of the present systematic review were to explore the prevalence of migraine with anxiety exclusively and determine if and why there are likely to be differences across genders. Introduction Migraine is a very common neurological disorder and cause of productive disability worldwide that is more frequent in women of childbearing age than males. Previous studies have frequently demonstrated the comorbidity of migraine and other psychiatric disorders. Although the prevalence of migraine across gender is well established there are few if any systematic review on the prevalence of migraine comorbidity with anxiety cross-genders. Methods The present systematic review included prevalence studies, clinic-based or cohort studies if they were reporting the frequency of migraine with anxiety within the study sample. Eleven studies were included in the review after screening by two independent reviewers. Studies included participants who were 16 years and older diagnosed with migraine. Results The main findings of this review indicated that anxiety is a major comorbidity of migraine worldwide, with a wide range (16-83%) of prevalence and a mean of approximately 43% of patients experiencing comorbid symptoms. Subjective anxiety symptoms appear to show to be greater among males with migraine than females which could be attributable to both environmental and/or hormonal and genetic predispositions. Conclusions The results reemphasize the high prevalence of migraine and comorbid anxiety symptoms worldwide while showing that although far more prevalence among women in general commodity of migraine with anxiety unfolds a different gender difference. The results highlight the significance of exploring the impact of existing and pre-existing comorbid conditions of patients with migraines and further consideration into their diagnostic and treatment strategies.